Trends in High-Speed Data NetworksDOI: 10.14209/jcis.1993.1 - A. Rodrigues, Manoel (Journal of Communication and Information Systems, 2015)
In this paper we present a discussion of the trends in high-speed data networking. We describe some of the factors that have been instrumental in the development of today's needs for high-speed interconnection. Based on the experience with the Internet, we find that a successful (high-speed) data networking solution should be offered as a set of services that are valuable to the user, instead of relegating the burden of creating value out of the technology to the user. In light of that, we describe some of the services that have been developed to address the specific needs of LAN applications, like Frame Relay (FR) and Switched Multi-megabit Data Service (SMDS), as well as some of the enabling technologies, like Distributed Queue Dual Bus (DQDB) and Asynchronous Transfer Mode (ATM). We also discuss the B-ISDN efforts towards providing a general purpose platform for supporting (current and future) applications having high-speed interconnection needs. We finalize the paper with a discussion of technology challenges for supporting applications with widely different high-speed requirements.